2014
DOI: 10.3109/00207454.2014.971788
|View full text |Cite
|
Sign up to set email alerts
|

Palmar cutaneous nerve conduction in patients with carpal tunnel syndrome

Abstract: The PCBm is not ideal as a comparator nerve for the neurophysiological diagnosis of CTS. The frequency of PCBm abnormality in CTS patients may be related to the concomitant damage in both of these nerves. Additionally, the present findings may help explain, at least in part, why patients with CTS often exhibit sensory involvement beyond the classical median nerve sensory borders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This electrodiagnostic finding was expected to help explain sensory symptoms beyond the classic sensory distribution of the MN in patients with CTS. Similarly, in a study by Uluc et al [5], 56% patients with CTS showed abnormality of PCMBN conduction study. The results of these studies suggest that electrodiagnostic tests can help identify concomitant damage of the PCBMN in patients with CTS.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…This electrodiagnostic finding was expected to help explain sensory symptoms beyond the classic sensory distribution of the MN in patients with CTS. Similarly, in a study by Uluc et al [5], 56% patients with CTS showed abnormality of PCMBN conduction study. The results of these studies suggest that electrodiagnostic tests can help identify concomitant damage of the PCBMN in patients with CTS.…”
Section: Discussionmentioning
confidence: 57%
“…There have been several studies on electrodiagnostic and surgical findings of concomitant entrapment neuropathy of the PCBMN in patients with CTS [ 5 , 6 , 15 ]. Imai et al [ 6 ] compared preoperative sensory conduction studies with operative findings in patients with CTS who complained of dysesthesia of the thenar eminence and showed that the sensitivity and specificity of the electrophysiologic study were 75% and 100%, respectively, with a relatively high accuracy in demonstrating entrapment of the PCBMN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations